2001
DOI: 10.1002/1097-0142(20010715)92:2<446::aid-cncr1341>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tumor-associated antigen RCAS1 correlates significantly with poor prognosis in nonsmall cell lung carcinoma

Abstract: BACKGROUND RCAS1 is a recently discovered antigen molecule expressed on the membrane of cancer cells, and it acts as a ligand for a putative receptor present on immune cells such as T, B and NK cells. It has been suggested that RCAS1 expression is related to the escape of tumors from immune surveillance. In this study, the relation between RCAS1 expression and various clinicopathologic variables, including patient prognosis, was investigated in lung carcinoma through immunohistochemical analysis. METHODS One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 20 publications
1
52
0
3
Order By: Relevance
“…Izumi et al (2001) reported that RCAS1 expression was positive for 48 of 102 non-small-cell lung carcinoma patients (47.1%) and was significantly correlated with advanced stage, poor differentiation and poor prognosis. Ito et al (2003) reported that RCAS1 overexpression was more frequently observed in anaplastic carcinomas than well-differentiated carcinoma in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Izumi et al (2001) reported that RCAS1 expression was positive for 48 of 102 non-small-cell lung carcinoma patients (47.1%) and was significantly correlated with advanced stage, poor differentiation and poor prognosis. Ito et al (2003) reported that RCAS1 overexpression was more frequently observed in anaplastic carcinomas than well-differentiated carcinoma in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Others reported that RCAS1 is associated with poor prognosis and/or advanced stage in various human cancers (Sonoda et al, 1996;Kaku et al, 1999;Izumi et al (2001); Nakakubo et al, 2002). However, the expression of EBAG9 and its clinical significance have not been examined in epithelial ovarian cancer.…”
mentioning
confidence: 99%
“…Expression of RCAS1 correlates with invasion or progression in several carcinomas (2,9,10). In addition, RCAS1 expression is associated with poor prognosis in uterine, lung, gallbladder, pancreas, and esophageal carcinoma (11)(12)(13)(14)(15). Although previous studies suggested that RCAS1 is also expressed in colorectal carcinoma cells, the relationship between RCAS1 expression and prognosis in colorectal carcinomas is not known at present.…”
mentioning
confidence: 99%
“…Patients with RCAS1 overexpression had a poorer survival than those with normal RCAS1 expression and those with positive RCAS1 expression (Po0.0001). In previous studies, RCAS1 expression was associated with poorer clinical prognosis for uterine cervical adenocarcinoma and non-small-cell lung carcinoma (Kaku et al, 1999;Iwasaki et al, 2000;Izumi et al, 2001). RCAS1 expression has also been reported to correlate with tumour progression or the invasive tendency of uterine cervical, gastric, skin, and hepatocellular carcinomas (Sonoda et al, 1998;Kubokawa et al, 2001;Noguchi et al, 2001;Takahashi et al, 2001).…”
Section: Discussionmentioning
confidence: 91%